2020
DOI: 10.1093/cercor/bhaa167
|View full text |Cite
|
Sign up to set email alerts
|

Brain Network Segregation and Glucose Energy Utilization: Relevance for Age-Related Differences in Cognitive Function

Abstract: The human brain is organized into segregated networks with strong within-network connections and relatively weaker between-network connections. This “small-world” organization may be essential for maintaining an energetically efficient system, crucial to the brain which consumes 20% of the body’s energy. Brain network segregation and glucose energy utilization both change throughout the lifespan. However, it remains unclear whether these processes interact to contribute to differences in cognitive performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 68 publications
2
38
1
Order By: Relevance
“…Since neurons require high energy consumption to function normally, notably to drive a sodium gradient across the cell membrane via the Na+/K+-ATPase, the cell's energy production capability is vital for the execution of brain physiological functions (Dienel, 2019 ). Although previous research demonstrates that energy metabolism is altered in the aged brain compared to the young adult brain, a more specific and quantitative description of energy metabolic pathways in the brain (Hoyer, 1990 ; Camandola and Mattson, 2017 ; Drulis-Fajdasz et al, 2018 ; Manza et al, 2020 ), especially in animals completing behavioral tasks, is not well-understood. Glucose is the major energy resource responsible for supporting brain activity under non-starvation conditions (Mergenthaler et al, 2013 ; Dienel, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since neurons require high energy consumption to function normally, notably to drive a sodium gradient across the cell membrane via the Na+/K+-ATPase, the cell's energy production capability is vital for the execution of brain physiological functions (Dienel, 2019 ). Although previous research demonstrates that energy metabolism is altered in the aged brain compared to the young adult brain, a more specific and quantitative description of energy metabolic pathways in the brain (Hoyer, 1990 ; Camandola and Mattson, 2017 ; Drulis-Fajdasz et al, 2018 ; Manza et al, 2020 ), especially in animals completing behavioral tasks, is not well-understood. Glucose is the major energy resource responsible for supporting brain activity under non-starvation conditions (Mergenthaler et al, 2013 ; Dienel, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…High within-network connectivity but low betweennetwork connectivity, called system segregation, is a key global feature associated with higher cognitive performance across the life-span 3,4 . During aging and disease, system segregation decreases 3,[5][6][7][8][9] (for review see 10,11 ), resulting in poorer cognitive functions 3,5,9,[12][13][14]15 (for review see 4 ). In contrast, relatively preserved system segregation enhances cognitive resilience to brain alterations in older adults 16 .…”
Section: Introductionmentioning
confidence: 99%
“…This 'dedifferentiation' of functional systems has been associated with age-accompanied differences in patterns of brain activity, worse cognitive and motor ability, lower energy metabolism and altered neurotransmitter levels (for example, refs. [43][44][45][46][47] ). Cross-sectional comparisons have also revealed that middle-aged adults with lower socioeconomic status (SES) (35-64 years of age) exhibit lower brain system segregation than that of their peers of the same age with higher SES 48 , suggesting that there may exist environmental determinants of brain network aging.…”
mentioning
confidence: 99%